On Explaining Individual and Corporate Culpability in the Global Climate Change Era - Smith, Ian A. 1975- (2013)
Humans are causing global climate change (GCC), and such climate change causes harms. Robin Attfield explained how individuals should be understood to be culpable for these harms. In this paper, I use a critical analysis of Attfield’s explanatory framework to explore further difficulties in accounting for corporate responsibility for these harms. I begin by arguing that there are some problems with his framework as it is applied to individuals that emit greenhouse gases (GHGs). I then show that it will be very difficult to extend this framework to corporations. This is not a criticism of Attfield’s work (as he does not discuss corporate responsibility for those harms associated with GCC), but it will serve to show the difficulty in philosophically explaining corporations’ moral culpability when it comes to these harms. In fact, one positive conclusion of this paper is that it highlights a new area of concern that has been ignored in discussions of corporate responsibilities—that of mediated responsibilities—which is how Attfield understands our responsibilities regarding GCC. The discussion of this concern will draw attention to another positive conclusion of this paper: the harms associated with CO2 are very unlike the harms associated with other airborne-emitted substances, which will indicate that we will need new ways of understanding how individuals and corporations are philosophically responsible for these harms. The final positive conclusion of this paper will be a discussion of what the constraints should be on new approaches to explaining our culpability.
Keywords: Individual culpability; Corporate Responsibility; Environmental Ethics; Business Ethics; Global climate change